2017
DOI: 10.1016/j.chemosphere.2017.02.072
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lead on physiological and antioxidant responses in two Vigna unguiculata cultivars differing in Pb-accumulation

Abstract: Lead (Pb) is one of the most toxic anthropogenic pollutants, occurring widely in both terrestrial and aquatic ecosystems, where it impairs plant growth and development. In this work, the effect of 0.5 mM EDTA-Pb was evaluated in two Vigna unguiculata cultivars (SV and SET), with the aim of detecting genotype/cultivar dependent changes in the physiological and anti-oxidant responses (CAT and APX) of a leguminous plant. The data showed that SV accumulated more Pb in roots while SET accumulated more in leaves, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Consequently, increased H 2 O 2 generation caused greater lipid peroxidation indicated by higher MDA contents. Lead-induced oxidative stress changes in morphology and structural properties of roots in different crops, resulting in a reduction of resistance, has also been demonstrated in other crop plants, e.g., Vigna unguiculata [45], O. sativa [39], B. napus [46], Zea mays [47], Vicia faba [48], Zygophyllum fabago [49], Triticum aestivum [50], and Medicago sativa [51]. Although some plants have developed an efficient antioxidant defense system to resist Pb-induced oxidative stress [51,52], excessive ROS generation results in disruption of the antioxidant defense mechanism, which is the major consequence of Pb toxicity [45].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Consequently, increased H 2 O 2 generation caused greater lipid peroxidation indicated by higher MDA contents. Lead-induced oxidative stress changes in morphology and structural properties of roots in different crops, resulting in a reduction of resistance, has also been demonstrated in other crop plants, e.g., Vigna unguiculata [45], O. sativa [39], B. napus [46], Zea mays [47], Vicia faba [48], Zygophyllum fabago [49], Triticum aestivum [50], and Medicago sativa [51]. Although some plants have developed an efficient antioxidant defense system to resist Pb-induced oxidative stress [51,52], excessive ROS generation results in disruption of the antioxidant defense mechanism, which is the major consequence of Pb toxicity [45].…”
Section: Discussionmentioning
confidence: 86%
“…CAT activity may vary depending on the plant species and severity of a stress. It has been documented that CAT activity elevated in leguminous crops, while it was reduced in rice under heavy metal stress conditions [45,68,69]. Moreover, CAT activity increased with a minor stress but decreased in severe conditions [50].…”
Section: Discussionmentioning
confidence: 99%
“…After 90 days, the whole plants were harvested, after which the roots and leaves were separated and dried at 65˚C for 72 h to a constant weight to measure metal concentrations. The root, stem and leaf samples were digested in HNO 3 -HClO 4 , and the concentrations of Pb and Cd were determined via an atomic absorption spectrophotometer (AA-7000, Shimadzu, Japan) [6,38]. To explore the accumulation and transformation of Pb and Cd in the roots, stems and leaves, the bioaccumulation factor (BCF) and the translocation factor (TF) were calculated as follows [3]:…”
Section: Metal Content Analysis Of Plantsmentioning
confidence: 99%
“…They are highly toxic and pose a threat to plants and animals (including humans) by affecting their normal growth and health [4,5]. Heavy metals are absorbed mainly through the roots of plants and either remain there or are translocated to the shoots and into cells [6]. For most plant species, roots represent a barrier for metals.…”
Section: Introductionmentioning
confidence: 99%
“…Acid rain pollution could have effects on plant diseases by altering physiological metabolism and/or disease resistance systems of the host [ 17 , 18 ]. The antioxidant system appears especially sensitive to acid rain [ 10 , 19 , 20 ]. Previous studies have shown that P. oryzae combined with acid rain can induce rice plants to activate the defense system, improve the activity of plant peroxidases (POD) and phenylalanine ammonia-lyase (PAL), and stimulate the production of polyphenolic compounds, thus improving the plant resistance to stress [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%